The place of the endothelial component in the pathogenesis of influenza A - A. I. Vereschagina; E. V. Nikitin (Kazimierz Wielki University, 2018)
Influenza A viruses are genetically diverse and the most unpredictable variable pathogens. It is a dangerous and poorly managed infection, able to reassort, with a high probability of developing urgent conditions, complications and death at any age. The objective: to determine the diagnostic value of CEC in influenza A. Materials and methods: There were 158 influenza A patients included in the survey presented. Observation period - 2015-2018. The 1st group included 32 patients with a mild flu course, the 2nd group - 62 patients with moderate flu, and the 3rd group - 64 patients with a severe flu and mild pneumonia. The severity was determined by clinical manifestations and the presence of complications. Exclusion criteria from the study: age under 18 and over 45 y.o., pregnancy and severe somatic pathology. The control group consisted of healthy volunteers - 30 persons, similar in sex and age with a patient's group. Conclusions. It was established that endothelium damage occurs even at mild course of influenza A. Severe influenza infection is accompanied by a massive endothelial damage with the development of endothelial dysfunction. Determination of circulating endothelial cells in blood is a simple and reliable indicator of the disease severity and its complications development.